MAGnesium‐based bioresorbable scaffold and vasomotor function in patients with acute ST segment elevation myocardial infarction: The MAGSTEMI trial: Rationale and design. Issue 1 (9th September 2018) - Brugaletta, Salvatore; Cequier, Angel; Alfonso, Fernando; Iñiguez, Andrés; Romaní, Sebastian; Serra, Antonio; Salinas, Pablo; Goicolea, Javier; Bordes, Pascual; del Blanco, Bruno García; Hernández‐Antolín, Rosana; Pernigotti, Alberto; et al.
Abstract: Aim: Use of a Bioresorbable Scaffolds (BRS) either in clinical practice or in the setting of an acute myocardial infarction (MI) is controversial. Despite an overall high rate of thrombosis, vascular healing response following BRS implantation tend to superiority as compared to metallic drug‐eluting stent in ST‐segment elevation myocardial infarction (STEMI) patients. We sought to compare the in‐stent/scaffold vasomotion between metallic BRS and sirolimus eluting stent (SES) at 12‐month angiographic follow‐up in the setting of patients with STEMI treated by primary PCI. Study design: This is an investigator‐driven, prospective, multicenter, randomized, single blind, two‐arm, controlled trial (ClinicalTrials.gov number: NCT03234348). This trial will randomize ~148 patients 1:1 to SES or BRS. Primary end‐point is the in‐stent/scaffold change in mean lumen diameter after nitroglycerin administration at 12‐month angiographic follow‐up. Besides, patient‐oriented combined endpoint of all‐cause death, any MI, and any revascularization, together with scaffold/stent thrombosis rate and device‐oriented endpoint of cardiac death, target vessel (TV)‐MI and TVR at 1 year will be also evaluated. Clinical follow‐up will be scheduled yearly up to 5 years. Conclusion: This trial will shed light on the vascular vasomotion following BRS implantation in the complex scenario of STEMI.